An analytical model for peeling behaviors at the particle-polymer interface in hard-magnetic soft materials - Cao, Gongqi; Jin, Yuchen; Zhang, Jiguang; Xue, Zhangna; Liu, Jianlin (Applied mathematics and mechanics, 2025)
Hard-magnetic soft materials exhibit significant shape morphing capabilities under non-contact magnetic actuation, yet their particulate composition tends to compromise material toughness. To quantify particle-matrix interactions, we present a mechanics model describing the energy functional of planar magnetic composites. Through the Fourier series, the analytical solutions for stress distribution and interfacial peeling length of a single particle-polymer unit are derived with the Rayleigh-Ritz method under uniaxial tension. The calculated results of stress fields without the magnetic field agree well with those of the finite element method. The effects of external magnetic field strength and particle content on the stress distribution and peeling length are fully explored, and the enhanced analytical outcomes are obtained through numerical prediction. These insights can be used to validate the reliability of engineering designs, including adaptive structures, micro-electro-mechanical sensors, and soft robotic systems.